(untitled) (Sport and Exercise Psychology, 2026)
Using a huge variety of vocalizations by tennis players has become an incresaing attitude, both at a competitive and amateur level. The real usefulness of this habit in the execution of the athletic gesture is much debated: if on one hand it is believed that it is useful in the timing of the kinetics of the shot, consequently improving its effectiveness, on the other hand is undoubtably disturbing for the opponent. The two factions remain today very far from a meeting point that is more necessary than ever in relation to the purely ethical aspects of sports activity, considering that psychological and technical needs of those practicing this habit clash with the opponent attitude, seeing his concentration lowered when responding to the shot.